Determination of Factors Affecting Workers' Compliance With Occupational Health and Safety Culture in the IV Palu Bridge Construction Project of PT Waskita Karya (Persero) TBK - A. Ferina Herbourina Bonita; Rifdah Wardani; A. Suci Setiani Annisa; Yusniar Anggraeny; Roswati, Roswati; Ummu Khaerat Rahmawan (Sean Institute, 2025)
This study aims to analyze factors related to worker compliance in implementing occupational safety and health (OHS) culture in the Palu City Bridge Construction Project Area IV at PT. Waskita Karya (Persero) Tbk. The study used a quantitative design with a cross-sectional approach. The study sample consisted of 119 construction worker respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using univariate and bivariate tests. The results showed that knowledge (p=0.303) and work experience (p=0.592) were not significantly related to worker compliance in implementing an OHS culture. In contrast, supervision (p=0.001) was shown to have a significant relationship to worker compliance. These findings emphasize the importance of increasing supervision in the work environment, one of which is through the addition of safety officers in each project area, to strengthen the implementation of an OHS culture in the construction sector.